Parallel Algorithms to Set Up the Benes Permutation Network - Nassimi, D; Sahni, S (IEEE transactions on computers, 1982)
A parallel algorithm to determine the switch settings for a Benes permutation network is developed. This algorithm can determine the switch settings for an N input/output Benes network in 0(log 2 N) time when a fully interconnected parallel computer with N processing elements is used. The algorithm runs in 0(N½) time on an N ½ × N ½ mesh-connected computer and 0(log 4 N) time on both a cube connected and a perfect shuffle computer with N processing elements. It runs in 0(k log 3 N) time on cube connected and perfect shuffle computers with N 1+1/k processing elements.